Electroporation Knows No Boundaries: The Use of Electrostimulation for siRNA Delivery in Cells and Tissues. (September 2015) - Luft, Christin; Ketteler, Robin
The discovery of RNA interference (RNAi) has enabled several breakthrough discoveries in the area of functional genomics. The RNAi technology has emerged as one of the major tools for drug target identification and has been steadily improved to allow gene manipulation in cell lines, tissues, and whole organisms. One of the major hurdles for the use of RNAi in high-throughput screening has been delivery to cells and tissues. Some cell types are refractory to high-efficiency transfection with standard methods such as lipofection or calcium phosphate precipitation and require different means. Electroporation is a powerful and versatile method for delivery of RNA, DNA, peptides, and small molecules into cell lines and primary cells, as well as whole tissues and organisms. Of particular interest is the use of electroporation for delivery of small interfering RNA oligonucleotides and clustered regularly interspaced short palindromic repeats/Cas9 plasmid vectors in high-throughput screening and for therapeutic applications. Here, we will review the use of electroporation in high-throughput screening in cell lines and tissues.